Local contact characteristics of threaded surfaces in a planetary roller screw mechanism. Issue 1 (2nd January 2020) - Ma, Shangjun; Wu, Linping; Liu, Geng; Fu, Xiaojun
Abstract: This study investigates the local contact characteristics of the threaded surface meshing of a planetary roller screw mechanism (PRSM). First, according to the threaded surface structure and threaded surface meshing characteristics, expressions for the principal curvature and principal direction of the contact ellipse at a contact point are derived based on the differential geometry theory. Next, based on a force analysis and threaded surface equations, an analytical model is established to calculate the dimensions and principal vector direction of contact ellipses on threaded surfaces. The elastic deformation and maximum contact stress are determined using Hertz elastic contact theory. Then, finite element (FE) numerical models for a single pair of threads at the screw–roller interface and the roller–nut interface are developed to calculate the contact area and maximum contact stress. The results are compared with those of the analytical model to demonstrate the validity of the analytical model. Finally, based on the analytical model proposed in this article, the local contact characteristics of threaded surfaces with various thread pitches, flank angles, and profile radii of roller threads are analyzed in detail.